Simplified method for rapid seismic assessment of older R.C. buildings. (1st January 2018) - Pardalopoulos, Stylianos I.; Pantazopoulou, Stavroula J.; Lekidis, Vasilios A.
Highlights: Extension of the RSA procedure to more building types. Improvement and simplification of the equations used in the RSA procedure. Addition of closed forms for determination of the seismic demand in terms of PGA. Presentation of an evaluation flow chart used for field assessment. Abstract: After several years of progress in earthquake design procedures, existing reinforced concrete buildings that fall short of modern standards still represent the vast majority of the built environment. Poorly reinforced concrete structures are a threat to human life – an undeniable fact witnessed time and again during strong earthquakes throughout the world. Structures fail when subjected to deformation demands greater than their deformation capacity, thereby losing their ability to support the overbearing load. Efforts are focused in the development and simplification of direct assessment procedures that may be used to spot the likely collapse candidates from among the large inventory of existing construction. In this paper, simple procedures by which to estimate seismic demands and seismic capacities are used as a basis for the development of an evaluation flow chart that may be used by site engineers as a guide for field assessment. The demand in terms of peak lateral drift and the value of peak ground acceleration that the structure may support with little damage are expressed in closed form using simple geometric and material characteristics of the structure. The same tools may be used to guide the selection of a pertinent retrofit strategy that would eliminate the formation of a collapse mechanism in the structure. Practical application examples of seismic assessment and evaluation conducted on existing reinforced concrete buildings that suffered different levels of damage during past strong earthquakes are included for illustration.